Cost‐effectiveness of new antiviral regimens for treatment‐naïve U.S. veterans with hepatitis C. Issue 2 (21st December 2015) - Chidi, Alexis P.; Rogal, Shari; Bryce, Cindy L.; Fine, Michael J.; Good, Chester B.; Myaskovsky, Larissa; Rustgi, Vinod K.; Tsung, Allan; Smith, Kenneth J.
Abstract : Recently approved, interferon‐free medication regimens for treating hepatitis C are highly effective, but extremely costly. We aimed to identify cost‐effective strategies for managing treatment‐naïve U.S. veterans with new hepatitis C medication regimens. We developed a Markov model with 1‐year cycle length for a cohort of 60‐year‐old veterans with untreated genotype 1 hepatitis C seeking treatment in a typical year. We compared using sofosbuvir/ledipasvir or ombitasvir/ritonavir/paritaprevir/dasabuvir to treat: (1) any patient seeking treatment; (2) only patients with advanced fibrosis or cirrhosis; or (3) patients with advanced disease first and healthier patients 1 year later. The previous standard of care, sofosbuvir/simeprevir or sofosbuvir/pegylated interferon/ribavirin, was included for comparison. Patients could develop progressive fibrosis, cirrhosis, or hepatocellular carcinoma, undergo transplantation, or die. Complications were less likely after sustained virological response. We calculated the incremental cost per quality‐adjusted life year (QALY) and varied model inputs in one‐way and probabilistic sensitivity analyses. We used the Veterans Health Administration perspective with a lifetime time horizon and 3% annual discounting. Treating any patient with ombitasvir‐based therapy was the preferred strategy (35, 560; 14.0 QALYs). All other strategies were dominated (greater costs/QALY gained than more effective strategies). Varying treatment efficacy, price, and/or duration changed the preferred strategy. In probabilistic sensitivity analysis, treating any patient with ombitasvir‐based therapy was cost‐effective in 70% of iterations at a 50, 000/QALY threshold and 65% of iterations at a 100, 000/QALY threshold. Conclusion : Managing any treatment‐naïve genotype 1 hepatitis C patient with ombitasvir‐based therapy is the most economically efficient strategy, although price and efficacy can impact cost‐effectiveness. It is economically unfavorable to restrict treatment to patients with advanced disease or use a staged treatment strategy. (Hepatology 2016;63:428–436)